Factors influence organization management towards using electronic recruitment strategy - Abdulhussean, Sanaa Abdulkarim (2014)
Recruitment is a set of activities and processes used to obtain a sufficient number of people who are eligible and can legally work in an organization in a well-timed manner. Recruitment enables applicants as well as an organization to identify and select each other on the basis of mutual best interests. E-recruitment takes a place alongside traditional recruitment and even exceeds it in some countries. The current paper addresses the factors that affect organization management in engaging human resource management policies and strategies towards E-recruitment to attract human capital in order to compete and survive in the market. The aims of this study were to explore, identify and classify the factors that influence management towards E-recruitment as well as develop a conceptual framework. Seven factors, among which Faster Recruitment Process, Easier Administration, and Cost Reduction, were projected as findings of this paper.